Prediction of the filter no-reflow phenomenon in patients with angina pectoris by using multimodality: Magnetic resonance imaging, optical coherence tomography, and serum biomarkers. Issue 5 (May 2016) - Matsumoto, Kenji; Ehara, Shoichi; Hasegawa, Takao; Otsuka, Kenichiro; Yoshikawa, Junichi; Shimada, Kenei
Abstract: Background: Although the occurrence of no-reflow during percutaneous coronary intervention (PCI) has been shown to be associated with worse short- and long-term clinical outcomes, the clinical relevance of preventing flow deterioration by using the filter-based distal protection devices (DPDs) is controversial. We investigated predictors of the filter no-reflow (FNR) phenomenon during PCI by using multimodality, such as hyperintense plaques (HIPs) in the coronary artery on T1-weighted imaging (T1WI) non-contrast magnetic resonance, plaque composition by using optical coherence tomography (OCT), and serum biomarkers, in patients with angina pectoris. Methods and results: Fifty lesions from 50 patients with angina were examined. All patients underwent T1WI within 24 h before invasive coronary angiography was performed, and preinterventional OCT was performed on a native atherosclerotic culprit lesion. The signal intensity of coronary plaque to cardiac muscle ratio (PMR) was calculated on a standard console of the magnetic resonance system. Of the 50 lesions, 20 lesions showed FNR during PCI, while non-FNR was observed in 30 lesions. A cut-off value >1.85 of PMR had a sensitivity of 65%, a specificity of 93%, a positive predictive value of 87%, and a negative predictive value of 80% for identifying lesions with FNR. Multivariate analysis revealed that the presence of HIPs with PMR >1.85 ( p  = 0.008) was the only independent predictor of the FNR phenomenon during PCI. Conclusions: This study shows that the presence of HIPs with PMR >1.85 on T1WI was a novel independent predictor of the FNR phenomenon during PCI in angina patients. This result may help in identifying high-risk lesions for no-reflow to deploy filter-based DPDs.